Gross anatomical observations on the tongue of an adult white fallow deer - Sarma, M; Choudhury, K B Dev; Sarma, K K; Gogoi, B (The Indian Journal of Animal Sciences, 2011)
Gross anatomy oftongue ofwhite fallow deer was studied.Â